Analysis of the Influence of Tobacco Production and Consumption Tobacco on Volume of Tobacco Export with the Excise Tax on Tobacco as a Moderating Variable in Indonesia - Tsaqif Fadhlilhaq; M. Taufiq (International Journal of Economics, Business and Innovation Research, 2025)
This study analyzes the impact of tobacco production and domestic consumption on Indonesia’s tobacco export volume, with the excise tariff as a moderating variable. Using annual data from 2008 to 2023, the research applies multiple linear regression and Moderated Regression Analysis (MRA). Results indicate that production positively and significantly affects exports, while consumption has a significant negative effect. However, the tobacco excise tariff does not significantly moderate these relationships. These findings highlight that production and consumption directly influence export performance, whereas the current excise policy is ineffective as a moderating tool. The study offers important insights for improving tobacco trade policy and boosting the competitiveness of Indonesia’s tobacco industry in international markets.